2004
DOI: 10.1136/ijgc-00009577-200403000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Risk of progression in complex and atypical endometrial hyperplasia: clinicopathologic analysis in cases with and without progestogen treatment

Abstract: In most cases, the endometrioid adenocarcinoma of the endometrium is preceded by hyperplasia with different risk of progression into carcinoma. The original histologic slides from 560 consecutive cases with complex and atypical hyperplasia were re-examined to assess the interobserver-correlation. The hyperplasias were analyzed separately for their likelihood of progression to carcinoma in patients with and without progestogen hormonal therapy. In all cases, a fractional re-curreting was performed to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 5 publications
1
18
0
3
Order By: Relevance
“…Further support for this conclusion was obtained by Horn et al [40] who, after using the WHO94 classification, reached an overall (interobserver) correlation of 90% which is far better than the overall interobserver agreement of the study of Bergeron et al (70-82%) [40]. Kurman et al [35], Ferenczy and Gelfand [36] and Lacey et al [39] reported comparable results, as these have been analysed in "Classification schemes of endometrial hyperplasia: from anarchy to WHO".…”
Section: Reliability and Reproducibility Of Whosupporting
confidence: 61%
See 4 more Smart Citations
“…Further support for this conclusion was obtained by Horn et al [40] who, after using the WHO94 classification, reached an overall (interobserver) correlation of 90% which is far better than the overall interobserver agreement of the study of Bergeron et al (70-82%) [40]. Kurman et al [35], Ferenczy and Gelfand [36] and Lacey et al [39] reported comparable results, as these have been analysed in "Classification schemes of endometrial hyperplasia: from anarchy to WHO".…”
Section: Reliability and Reproducibility Of Whosupporting
confidence: 61%
“…Despite claims to the contrary, these morphological features could be recognized and reproduced with a fair degree of precision by several independent groups of workers [35,36,39,40,68].…”
Section: The Who94 Classification At a Second Lookmentioning
confidence: 99%
See 3 more Smart Citations